TIME COURSE OF BOTULINUM TOXIN ANALGESIA IN PERIPHERAL NEUROPATHIC PAIN: A SYSTEMATIC REVIEW AND META-ANALYSIS - Endang Ulupi Khoirunnisa; Yessi Mekarsari; Sih Reka Prawidya (Magna Neurologica, 2026)
Background: Peripheral neuropathic pain (PNP) is frequently refractory to systemic therapies. Botulinum toxin (BTX) has emerged as a targeted option, but its time course of analgesic effect remains incompletely defined. Objective: To characterize the onset, peak, and durability of BTX analgesia in PNP. Methods: A systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted according to PRISMA guidelines. A search was performed on December 19, 2025, covering studies published from 2006 to 2025. Included etiologies comprised diabetic neuropathy, trigeminal neuralgia, postherpetic neuralgia, and other PNP conditions. Pain outcomes were synthesized across predefined time windows: early (≤4 weeks), intermediate (6–12 weeks), and late (≥24 weeks). Random-effects meta-analyses using standardized mean differences (SMDs) were conducted at approximately 4 and 12 weeks. Results: Eighteen RCTs were included (n=916); four (n=129) and three (n=99) contributed to the 4- and 12-week meta-analyses, respectively. BTX-A significantly reduced pain versus placebo at 4 weeks (SMD −2.79, 95% CI −4.67 to −0.90; I² = 93%) and 12 weeks (SMD −2.54, 95% CI −4.55 to −0.53; I² = 92%). Analgesia began within 1–2 weeks and peaked at 6–12 weeks. Excluding one outlier reduced heterogeneity from I² = 92% to 55% while preserving significance. Evidence beyond 24 weeks was limited. Conclusion: BTX-A demonstrates a time-dependent and etiology-specific analgesic effect, with onset within 1–4 weeks, peak at 6–12 weeks, and waning after 12–16 weeks. These findings inform patient counselling and reinjection planning, typically at approximately 3-month intervals.